2006
DOI: 10.4049/jimmunol.176.8.5069
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-Specific MHC Class II Tetramer+ Cells Are Detectable in Allergic, but Not in Nonallergic, Individuals

Abstract: Allergen-specific cells are present in very low frequency in peripheral blood of humans, and differ in function in allergic and nonallergic individuals. We report in this study that soluble class II MHC tetramers can be used to directly identify and study such allergen epitope-specific CD4+ T cells in humans. We identified the major antigenic epitope of rye grass allergen Lol p 1 in HLA-DRB1*0401 individuals using HLA-DR*0401 transgenic mice and peripheral blood cells from HLA-DR*0401 individuals. Using DRB1*0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
72
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 22 publications
8
72
2
Order By: Relevance
“…Bet v 1-specific T cells isolated from BP allergic patients secrete, as expected, mostly IL-5 and IL-10, but not IFN-␥. These data are consistent with other studies (15,32,50,56), as well as with our analysis identifying predominantly Th2 clones in the peripheral blood of allergic patients (Table III) (12,30,50,51). The magnitude of the Th1 vs Treg cell response to Bet v 1 observed in the present study was unexpected, but it supports a predominant role of immune deviation toward IFN-␥ production to establish allergen-specific tolerance, as proposed recently by others (57).…”
Section: Cd4supporting
confidence: 81%
See 2 more Smart Citations
“…Bet v 1-specific T cells isolated from BP allergic patients secrete, as expected, mostly IL-5 and IL-10, but not IFN-␥. These data are consistent with other studies (15,32,50,56), as well as with our analysis identifying predominantly Th2 clones in the peripheral blood of allergic patients (Table III) (12,30,50,51). The magnitude of the Th1 vs Treg cell response to Bet v 1 observed in the present study was unexpected, but it supports a predominant role of immune deviation toward IFN-␥ production to establish allergen-specific tolerance, as proposed recently by others (57).…”
Section: Cd4supporting
confidence: 81%
“…Our results are in agreement with several studies demonstrating that healthy individuals can mount allergen-specific T cell responses (49 -52). In contrast, a recent study suggested that MHC class II peptide tetramers could detect T cell responses to the Lol p 1 grass pollen allergen in allergic but not in healthy individuals (15). Whereas it cannot be excluded that distinct seasonal allergens may elicit different types of immune responses, we can also possibly explain this discrepancy by the fact that we used in our study a potent in vitro stimulation protocol to expand rare allergen-specific T cell progenitors, relying on a Bet v 1 141-155 -Ii-Key conjugate peptide mix.…”
Section: Cd4mentioning
confidence: 90%
See 1 more Smart Citation
“…In order to efficiently monitor this latter pathway, various lymphocyte activation assays have been used, often involving the activation or proliferation of CD4 ϩ T cells in vitro as an indirect measure of antigen-specific responses. With the development of pMHC class II tetramers, it is now possible to directly assay the CD4 ϩ T-cell population for antigen-specific phenotypes (2,3,7,(12)(13)(14)22).…”
mentioning
confidence: 99%
“…However, in striking contrast to other allergens that contain multiple T cell epitopes (11)(12)(13), Art v 1 harbors only one single immunodominant epitope, Art v 1 [25][26][27][28][29][30][31][32][33][34][35][36] (KCIEWEKAQHGA), located in the defensin domain and recognized by 85% of Art v 1-reactive mugwort pollenallergic patients. The minimal epitope in Art v 1 [25][26][27][28][29][30][31][32][33][34][35][36] consists of 5-10 aa, and 3-5 aa within this core region have been shown to be relevant for T cell proliferation depending on the clonotypic TCR (14). The presentation of Art v 1 [25][26][27][28][29][30][31][32][33][34][35][36] has been shown to be HLA-DR-restricted (10,14).…”
mentioning
confidence: 99%